KAJIAN PEMANFAATAN TANAMAN BERKHASIAT OBAT PADA SISTEM PENGOBATAN TRADISIONAL MASYARAKAT DI PROVINSI MALUKU UTARA - Muhammad Haji Noh; Monissa A. Hi. Djafar; Hamidah Rahman; Badryah Abbas; Musiana . (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2020)
Traditional medicine is a part of culture and it is valued as a local wisdom of the community. Knowledge about medicinal uses of plants is generally passed down from generation to generation both verbally and from ancient manuscripts found from various regions in Indonesia. In North Maluku, there are several traditional medical practices using medicinal plants that are still ongoing.This study aims to obtain a descriptive data of traditional medical practices using medicinal plants in North Maluku using a systematic review method. Scientific data was obtained from online search on Google Scholar. The keywords used are "utilization of traditional medicine in North Maluku", "traditional treatment of North Maluku" and "utilization of herbal in North Maluku".There is no time limit for articles that were reviewed. The search results obtained ten articles that report the practice of traditional medicine using medicinal plants in different research locations.Plants that were most widely used were papaya (Carica papaya) for the treatment of malaria. The results also showed that there was still a lack of research reporting on traditional medical practices among tribes/ communities in North Maluku.